2
$\begingroup$

I have found confronting information on other websites and thus will ask my question here.

Is the following conversion legitimate?

$$\sum_{k=1}^n\sum_{j=1}^nk\cdot j=\sum_{k=1}^nk\cdot\sum_{j=1}^nj$$

I have seen someone doing something similar on Matroids Matheplanet.

Thank you for your help.

Philipp

$\endgroup$
3
$\begingroup$

Yes.

Since $k$ is a multiplier not related to $j$, it can be "factored" out, resulting in the product of two summations.

Simple example, using $n=3$:

$$\text{LHS}=\sum_{k=1}^3\sum_{j=1}^3 k\cdot j=\sum_{k=1}^3 k+2k+3k=\sum_{k=1}^3 6k=6\sum_{k=1}^3 k=6(1+2+3)=36\\ \text{RHS}=\sum_{k=1}^3k\sum_{j=1}^3 j=(1+2+3)(1+2+3)=36$$

For the general case, $$\begin{align} \text{LHS}&=\sum_{k=1}^n\sum_{j=1}^n k\cdot j\\ &=\sum_{k=1}^n k+2k+3k+\cdots +nk\\ &=\sum_{k=1}^3 (1+2+3+\cdots+n)k\\ &=\sum_{k=1}^n \frac {n(n+1)}2k\\ &=\frac {n(n+1)}2\sum_{k=1}^nk\\ &=\frac {n(n+1)}2\cdot\frac {n(n+1)}2\\ &=\sum_{k=1}^n k\sum_{j=1}^n j \end{align}$$


Note: If $k$ is not a multiplier for the entire summand, then it cannot be "factored" out.

Example:

$$\sum_{k=1}^n\sum_{j=1}^n j+k\neq \sum_{k=1}^nk+\sum_{j=1}^nj$$

$\endgroup$
2
$\begingroup$

$$\sum_{k}\sum_{j}kj=\sum_{k}\left(k(1+2+3+...)\right)$$ $$=(1+2+3...+n)1+(1+2+3...+n)2+...+(1+2+3...+n)n$$ And $$\sum_{k}k\sum_{j}j=(1+2+3...+n)(1+2+3...+n)$$ Clearly, by distribution, the two are equal.

$\endgroup$
2
$\begingroup$

Since you have final sums, there is no problem. See $$ \sum_{k=a}^n\sum_{j=b}^m c_kd_j=\sum_{k=a}^n\left(\sum_{j=b}^m c_kd_j\right)= \sum_{k=a}^n\left(c_k\sum_{j=b}^m d_j\right)=\left(\sum_{k=a}^nc_k\right)\left(\sum_{j=b}^m d_j\right) $$ You just use the distributive law. At the first equation I added the brackets to clarify the meaning. Next $c_k$ is in the sum over $j$ like a constant. So you can exchange them. Finally the sum over j is independent of $k$ and you can exchange them again.

$\endgroup$
2
$\begingroup$

Yes

\begin{eqnarray} \sum_{k=1}^n\sum_{j=1}^nk\cdot j &=& \sum_{k=1}^n k \cdot (1+2+...+n)\\ &=&1(1+2+...+n)+2(1+2+...+n)+...+n(1+2+...+n )\\ &=& (1+2+...+n)(1+2+...+n)\\ &=&\sum_{k=1}^nk\cdot\sum_{j=1}^nj \end{eqnarray}

$\endgroup$
1
$\begingroup$

Trivia: $\Large\sum, \int, \newcommand{\derivative}[3] {\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \derivative{n}{y}{x}$ are linear operations.

What does it mean?

$\Large f(x)$ is linear if and only if

$$\Large f(x+y)=f(x)+f(y)$$

$$\Large f(ax)=a\cdot f(x)$$

Let

$$\large f(x)=\sum_{j=1}^nx$$

And

$$\large a=\sum_{k=1}^nk$$

So

$$\large f(ax)= \sum_{j=1}^n\left(\sum_{k=1}^nk\right)x$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.